Utilizing SS-OCT and 3D parametric modeling to enhance IOL position prediction in cataract patients with long axial length - Li, Chuang; Luo, Bin; Luo, Xiaoling; Zhang, Liying; Li, Qiang; Peng, Wei (Frontiers in Medicine, 2025)
PurposeThis study aimed to investigate the biological characteristics of the lens and explore the factors influencing the postoperative position of intraocular lens (IOL) using swept-source optical coherence tomography (SS-OCT) in cataract patients with long axial length (AL).MethodsThis retrospective study enrolled 110 cataract patients who underwent uneventful cataract surgeries. The preoperative and postoperative biometric parameters were obtained using IOLMaster 700. The average lens density (ALD) was analyzed using Fiji ImageJ. The biological characteristics of cataracts were analyzed using three-dimension (3D) parametric modeling software, Pro/Engineer Wildfire 5.0.ResultsThe lens equator position (LEP) showed positive correlation with the preoperative anterior chamber depth (ACD), lens equatorial diameter (LED), and lens vaulting (LV). The postoperative position of the IOL showed positive correlation with the preoperative ACD and LEP (r = 0.432, p < 0.05; r = 0.657, p < 0.05). The LEP demonstrated a higher correlation with the postoperative position of the IOL than with the preoperative ACD (p < 0.05). The LEP displayed the highest correlation with the postoperative position of the IOL (r = 0.686, p < 0.05) in the subgroup of ultra-long eyes (AL ≥ 28.0 mm).ConclusionThe LEP, derived from the SS-OCT and 3D parametric modeling, was a better predictor of postoperative IOL position than the preoperative ACD. This methodology provides a robust basis for accurately predicting the effective lens position in cataract patients with long AL.